Learning The Book Of Hujjah Ahlussunnah Wal Jamaah In Internalizing The Values Of Religious Moderation At The Shofa Marwa Patemon Pakusari Islamic Boarding School In Jember - Ahmad Dhiyaa Ul Haqq; Iqrar Hussain; Depict Pristine Adi (IJIBS, 2023)
Religious radicalism has entered various sectors of life, including the realm of education. For this reason, pesantren as a center for Islamic education must take a role in efforts to prevent religious radicalism by instilling the values of religious moderation. At Shofa Marwa Islamic Boarding School, Patemon Pakusari Jember strives to instill the values of religious moderation through the Study of the Book of Hujjah Ahlussunnah Wal Jamaah. The purpose of this study is to describe 1.Learning Objectives of the Book of Hujjah Ahlussunnah Wal Jamaah, 2.Stages of Learning the Book of Hujjah Ahlussunnah Wal Jamaah 3.The values of religious moderation are realized at the Shofa Marwa Patemon Pakusari Jember Islamic Boarding School. This research uses a descriptive qualitative approach with a type of field study research. Data collection using observation, interviews, and documentation. Data analysis using models from Huberman and Saldana includes Data Collection, Data Condensation, Data Display, and Conclutions. Test the validity of the data using source triangulation and triangulation techniques. The results of this research are 1) The purpose of learning the Book of Hujjah Ahlussunnah Wal Jamaah at Shofa Marwa Pakusari Islamic Boarding School Jember is to strengthen the foundation of student faith and protect and fortify students from radical ideas, both still in pesantren and those who have become alumni, and practice values that have been understood in individual and social life. 2) Internalization of the value of religious moderation through 3 prisoners, namely: a. Value Transformation Stage, by delivering material by the sequence of themes in the book through the band organ method, namely interpreting the book in Javanese pegon and providing a detailed explanation of the material taught directly to students. b. Value transaction stage, students read books and deposit readings from books that have been interpreted and explained by educators / ustadz or commonly referred to using the sorogan method combined with the Qowaid wa Tarjamah method and problem based learning. Transinternalization, educators / ustadz do conditioning and habituation to behave by values that have been understood and practiced together. The goal is to train students to understand values by perceived conditions and actualize values in their daily community life. 3.The values of religious moderation internalized through the study of the Book of Hujjah Ahlussunnah Wal Jamaah are a.Ishlah (Open Minded) b.Muwathanah love of homeland/Nationalism/National Commitment c.Tasamuh (tolerance) d.Al-La'Unf nonviolence e.I'tiraf al-'Urf (Pride in culture) or accommodating culture.